Development Of Granule Form Making Fertilizers In Muhammadiyah 3 Morowudi Gresik Vocational School - Efta Dhartikasari Priyana; Eko Budi Leksono; Said Salim Dahda (Universitas Muhammadiyah Gresik, 2020)
Fertilizer is the most important thing in terms of caring for plant growth. This was identified because fertilizer has nutrient mineral elements which are really needed by the plants themselves. Fertilizer itself is divided into organic and inorganic fertilizers. Still related to the type of fertilizer itself, in order to get plants with good quality and cultivation, the fertilizer given must be balanced because it is in line with the contents that exist in each type of fertilizer. Inorganic fertilizer or better known as chemical fertilizer is more popular with many people because of its practicality, but it should be remembered that excessive use of chemical fertilizers also have a negative impact on soil fertility. Therefore organic fertilizer still plays a role in the field of inorganic fertilizer in order to offset the need for soil itself. Understanding the importance of a balance between organic and inorganic fertilizers, the community service conducted by providing training in making Guano fertilizer at SMK Muhammadiyah 3 Morowudi Gresik was chosen to be applied. Guano fertilizer was chosen as an alternative to the addition of a companion formula rather than inorganic fertilizer because of its content which is rich in nitrogen, phosphorus, postasium which is needed by plants. Efforts to provide training to students of SMK Muhammadiyah 3 Morowudi Gresik are also expected to be able to boost cooperation than the students themselves in developing their potential to contribute to the community and schools